2022
DOI: 10.1051/0004-6361/202142431
|View full text |Cite
|
Sign up to set email alerts
|

Supernova remnant G46.8–0.3: A new case of interaction with molecular material

Abstract: Although the Galactic supernova remnant (SNR) G46.8–0.3 has been known for more than 50 yr, no specific studies of this source or its environment have been published to date. To make progress on this matter, we measured new flux densities from radio surveys and combined them with previous estimates carefully collected from the literature to create an improved and fully populated version of the integrated radio spectrum for G46.8–0.3. The resulting spectrum exhibits a featureless power-law form with an exponent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 74 publications
(67 reference statements)
1
4
0
Order By: Relevance
“…From H 2 infrared emission lines, Lee et al (2020) found a V LSR of 44 ± 1 km s −1 and obtained a kinematic distance of 5.4 ± 0.1 kpc, which are both consistent with values from H I. With combined CO-H I profiles, Supan et al (2022) provided evidence for environmental molecular clouds that are physically linked to the remnant at its center, the lower edge, and toward the bright regions on the top-left and lower-right rims on the far side of the SNR shell. Sun et al (2011a) observed SNR G46.8 − 0.3 at λ6 cm to be 8% polarized with an integrated polarized flux density of 595 ± 32 mJy and a spectral index of −0.54 ± 0.02 at ¢ 9.5 resolution.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…From H 2 infrared emission lines, Lee et al (2020) found a V LSR of 44 ± 1 km s −1 and obtained a kinematic distance of 5.4 ± 0.1 kpc, which are both consistent with values from H I. With combined CO-H I profiles, Supan et al (2022) provided evidence for environmental molecular clouds that are physically linked to the remnant at its center, the lower edge, and toward the bright regions on the top-left and lower-right rims on the far side of the SNR shell. Sun et al (2011a) observed SNR G46.8 − 0.3 at λ6 cm to be 8% polarized with an integrated polarized flux density of 595 ± 32 mJy and a spectral index of −0.54 ± 0.02 at ¢ 9.5 resolution.…”
Section: Resultssupporting
confidence: 65%
“…Lee et al (2019) observed H 2 line emission associated with the edges of regions of bright synchrotron emission for G43.3−0.2 and G39.2−0.3, which indicate a collision between the SNR shock and a dense molecular cloud. Similarly for G46.8−0.3, Supan et al (2022) observed an interaction between the forward shock and dense molecular clouds in the center of the SNR and the brightest regions along the edges. For each polarized SNR in this study, we associate depolarization in regions with bright Stokes I with an interaction between the SNR shock and nearby molecular clouds.…”
Section: Discussionmentioning
confidence: 59%
“…Therefore, the remnant may be associated with either the +19.4 or +59.3 km s −1 components. Note that there is H I absorption at the tangent point velocity toward this SNR detected by Sato (1979), Ranasinghe & Leahy (2018b), and Supan et al (2022), indicating that the SNR is at a far kinematic distance. The far kinematic distance of the +19.4 km s −1 component is estimated as 10.1 ± 0.6 kpc, and the kinematic distance of the +59.3 km s −1 component is estimated as 6.9 ± 0.5 kpc.…”
Section: Appendix a Individual Snrsmentioning
confidence: 73%
“…From H 2 infrared emission lines, Lee et al (2020) find a V LSR of 44 ± 1 km s −1 and obtain a kinematic distance to be 5.4±0.1 kpc which are consistent with values from HI. With combined CO-HI profiles, Supan et al (2022) provide evidence for environmental molecular clouds that are physically linked to the remnant at its centre, the lower edge, and towards the bright regions on the top-left and lower-right rims on the far side of the SNR shell. Sun et al (2011a) observed SNR G46.8−0.3 at λ6 cm to be 8% polarized with an integrated polarized flux density of 595±32 mJy and a spectral index of −0.54 ± 0.02 at 9.…”
Section: Methodsmentioning
confidence: 93%
“…Since we do not detect polarized emission from the brightest parts of the SNRs at λ21 cm, polarization observations at λ6 cm would confirm that depolarization in the bright regions is wavelength-dependent. Lee et al (2019) G46.8−0.3, Supan et al (2022) observe an interaction between the forward shock and dense molecular clouds in the centre of the SNR and the brightest regions along the edges. For each polarized SNR in this study, we associate depolarization in regions with bright Stokes I with an interaction between the SNR shock and nearby molecular clouds.…”
Section: Snr G411−03mentioning
confidence: 90%